INCOME TAXES AND CAPITAL INVESTMENT. - McIntire, L. B. (The Accounting Review, 1945)
It has been inferred by critics of the Federal Administration that Federal taxes have been imposed for some reason other than revenue. While there is enough truth in this inference to make it generally acceptable, still it must perhaps be admitted that revenue has been the primary purpose for Federal taxes. The charge has been made, and fairly, that "New Deal" taxes have brought about bad economic results. The cure for these bad results has been suggested to be "Taxation for revenue only" which suggestion carries the inference that tax laws should be framed without consideration of anything but the revenue to be obtained. The fallacy here is plain. It has been suggested recently from more than one quarter that the general welfare would be enhanced if accountants would take a more active interest in the field of economic thought and exert a benevolent influence on legislation affecting national and international economics. It should be recognized that productive enterprise is "the goose that lays the golden egg," and that capital investment is the fundamental element of this enterprise. Federal income taxes should not be discriminatory in their effect on such enterprise, rather enterprises should be encouraged to expand to the end that employment, goods, and services adequate to satisfy human needs and wants shall be provided.